Rocket, Cress and a Dash of Skirret: a Journey Through a Mare’s Nest - Lyman-Dixon, Anthony (Petits Propos Culinaires, 2014)
This article looks at the various cresses and their culinary and medical properties and discusses why it has often been under-explored by contemporary books about medieval foods. Although its inclusion in the medieval diet had a major impact on the health of those who ate it, cress was perceived as a lowly peasant food and that there wasn’t much one could do with it.